Critical thinking skills of Chemistry students by integrating design thinking with STEAM-PjBL - Lintang Rizkyta Ananda; Yuli Rahmawati; Fauzan Khairi (OmniaScience, 2023)
This project seeks to foster students' critical thinking abilities through the incorporation of Design Thinking with STEAM-PjBL in a chemistry redox process. 41 grade 10 students from a high school in Rangkasbitung, Banten, Indonesia participated in this study. Learning was facilitated by using a variety of online platforms, including Edmodo, Google Jamboard, and Zoom Meetings. Interviews, observations, journal reflection procedures, and researcher notes were used to gather qualitative data. The five steps of Design Thinking: empathize, define, ideate, prototype, and test, were used to facilitate learning (Plattner, 2010). Critical thinking skills were assessed through the indicators of Framing The Problem, Solution Finding, Self-Regulation, and Reflection, developed by Ucson & Rizona (2018). Based on the categories of Information Search, Creative Interpretation and Reasoning, Reflection, and Self-Regulation, the results demonstrate the development of students' critical thinking abilities to the advanced level. Design Thinking provides a way to more easily and actively create project-based solutions in solving contextual problems related to redox reaction of water pollution in the Ciujung River due to the use of detergent waste. Understanding the relationship of chemical concepts to daily life challenges the application of this approach. To challenge students' learning and help them acquire 21st-century abilities, STEAM-PjBL may be integrated with Design Thinking.